Activity of the adrenocortical system in rats with experimental diabetes - Olga Pavlovna Cherkasova; Natalya Vladimirovna Kuznetsova; Natalya Alexandrovna Pal'chikova; Vera Georgievna Selyatitskaya (Сахарный диабет)
Aim. To study the functional state of the adrenocortical system in experimental animals depending on severity of alloxan diabetes. Materials and methods. Diabetes in rats was induced by administering alloxan tetrahydrate at a dose of 17 mg/100 g b.w. Corticosteroids in plasma,adrenals, and 24-hr urine were measured by RIA, immunoenzyme assay, and HPLC. Hepatic aminotransferase activities were determined. Results. Durng the first week after induction of diabetes, the animals suffered metabolic disturbances and hypoinsulinemia the severity of which didnot significantly change up to day 30 Activation of adrenal glucocorticoid function (a rise in plasma corticosteron, urine and adrenal corticosteronand progesteron) occurred starting from days 8-9. Enhanced activity of hepatic aminotransferases confirmed physiological significance of elevatedblood corticosteron level. Conclusion. Physiological effects of glucocorticoids in the liver decreased by day 30 of experimental diabetes despite persisting disturbances in carbohydratemetabolism, probably due to reduced synthesis of corticosteron in adrenals and its concentration in blood.